2017
DOI: 10.18203/issn.2454-5929.ijohns20173038
|View full text |Cite
|
Sign up to set email alerts
|

Listening skill progress in children with cochlear implants in the first three months after implantation

Abstract: <p class="abstract"><strong>Background:</strong> Development of auditory skills is triggered as soon as cochlear implantation is done. Very few studies have reported development of listening skills in cochlear implanted children in the immediate period following the implantation. The present study aims to<strong> </strong>profile the development of auditory skills in children with cochlear implants during the first three months following implantation<span lang="EN-IN">. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The AVT approach includes individual diagnostic sessions emphasizing the use of hearing in meaningful and optimal situations hence emphasizing on developing hearing as an active sense ( Ling, 1993 ). It emphasizes facilitating and promoting the optimal acquisition of expressive language through listening ( Chatterjee et al., 2019 ; Nandurkar and Susmitha, 2017 ). The listening environment in AVT can be enhanced in various ways, such as having the therapist sitting in front of a child and using appropriate techniques including acoustic highlighting, pausing and providing alternatives ( Dornan et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The AVT approach includes individual diagnostic sessions emphasizing the use of hearing in meaningful and optimal situations hence emphasizing on developing hearing as an active sense ( Ling, 1993 ). It emphasizes facilitating and promoting the optimal acquisition of expressive language through listening ( Chatterjee et al., 2019 ; Nandurkar and Susmitha, 2017 ). The listening environment in AVT can be enhanced in various ways, such as having the therapist sitting in front of a child and using appropriate techniques including acoustic highlighting, pausing and providing alternatives ( Dornan et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted by Nadurkar and Susmitha to see the progress in listening skills of cochlear implant children suggests development of auditory skills triggers in first three months of cochlear implantation. 5 A study conducted by Dornan et al suggest that within nine months of auditory verbal therapy, there is a significant boost in linguistic skills of cochlear implant children and age appropriate linguistic skills can be achieved within 24 months. 6 Most and Peled in his study concluded that perception of supra-segmental features of speech in children with cochlear implant had not a significant effect on children with hearing aids.…”
Section: Discussionmentioning
confidence: 99%